Addiction to electronic games among middle school students: A field study in the General Directorate of Education in Baghdad / Third Rusafa - Nasir, Mohammed A. (Al-Adab Journal, 2022)
The addiction of a large segment of middle school students to electronic games has many negative repercussions, including academic failure due to the large amount of time devoted to playing at the expense of study, social isolation and poor communication with others, as well as health risks.The research community consisted of male and female middle school students (the second intermediate), in the General Directorate of Education in Baghdad / Al-Rusafa the third. As for the study sample, it was intentional and represented by (5) male schools, (5) female schools, and by (10) questionnaires For each middle school, the total number is (50) questionnaires for male schools, and (50) questionnaires for female schools. The study concluded that: Electronic games are a widespread and noticeably social phenomenon in middle schools. It is available to both male and female students of this study.As for the most important recommendations, they are: conducting more extensive, comprehensive and specialized studies from the current study, in order to come up with results and conclusions that would clarify the size of this problem and its causes, and to benefit from international and educational experiences that addressed this problem, or limited its danger, in order to overcome the negative effects of this problem now and in the future.